Intramyocardial dissection with concomitant left ventricular aneurysm as a rare complication of myocardial infarction: a case report - Liu, Chang-Cheng (J Geriatr Cardiol, 2016)
We describe a rare case of a 60-year-old woman suffering from intramyocardial dissection and left ventricular aneurysm secondary to acute myocardial infarction. A rare form of ventricular septal rupture resulted from intramyocardial dissection deterioration, which was identified during echocardiographic follow-up. Surgical repair under beating-heart cardiopulmonary bypass was successful.